The development path of the Republic of Uzbekistan is in the case of "Digital Uzbekistan 2030" (Zien Journal of Social Sciences and Humanities, 2022)
Currently, the transition of technology to the digitalization phase and the introduction of an artificial intelligence system have led to the formation not only of economic but also of the military system of many countries. The systematic phase of digitalization in the economy is considered in the case of the Republic of Uzbekistan.